+0  
 
0
87
1
avatar

 

a.) x^3 + 3x^2 - x = 3 

 

 

 

b.) b^3 - 4b^2 -21b = 0

 Dec 3, 2018
 #1
avatar+98196 
+1

a.) x^3 + 3x^2 - x = 3 

Subtract 3 from both sides

x^3 + 3x^2 - x - 3  = 0

Factor by grouping

x^2 (x + 3) - 1(x + 3) = 0

(x^2 - 1) ( x + 3) = 0

(x + 1) ( x - 1) ( x + 3) = 0

 

Setting each factor to 0 and solving for x produces

x = -1    or    x = 1    or     x = -3

 

 

 

b.) b^3 - 4b^2 -21b = 0

Factor as

b ( b^2  - 4b - 21) = 0

b (b - 7) ( b + 3) = 0

 

Setting each factor to 0  and solving for b produces

b = 0  or  b  = 7    or    b = -3

 

 

cool cool cool

 Dec 3, 2018

11 Online Users

avatar
avatar